2011
DOI: 10.1002/ppul.21576
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia and aspiration in children

Abstract: Aspiration is a significant cause of respiratory morbidity and sometimes mortality in children. It occurs when airway protective reflexes fail, especially, when dysphagia is also present. Clinical symptoms and physical findings of aspiration can be nonspecific. Advances in technology can lead to early diagnosis of dysphagia and aspiration, and, new therapeutic advances can significantly improve outcome and prognosis. This report first reviews the anatomy and physiology involved in the normal process of swallow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
2
15

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(137 citation statements)
references
References 178 publications
1
117
2
15
Order By: Relevance
“…Propping bottles up with a blanket or towel is discouraged because it prevents an infant from turning their head from the bottle when finished and also poses a significant choking hazard. 49,51 Once infants begin eating solid foods, the guidelines for nutrient quality do not differ materially from toddlerschildren should be consistently offered healthy foods, and unhealthy foods should be limited. Infant providers were nearly 9 times more likely to avoid serving sugary foods and 11 times more likely to avoid serving fast food to children than toddler providers.…”
Section: Discussionmentioning
confidence: 99%
“…Propping bottles up with a blanket or towel is discouraged because it prevents an infant from turning their head from the bottle when finished and also poses a significant choking hazard. 49,51 Once infants begin eating solid foods, the guidelines for nutrient quality do not differ materially from toddlerschildren should be consistently offered healthy foods, and unhealthy foods should be limited. Infant providers were nearly 9 times more likely to avoid serving sugary foods and 11 times more likely to avoid serving fast food to children than toddler providers.…”
Section: Discussionmentioning
confidence: 99%
“…54 However, in a small sample size study (N = 30), FEES was concluded to be a comparable technique to the VFSS for diagnosis and treatment of pediatric patients in the acute care setting. 55 FEES visualizes events at the pharyngeal stage in virtual isolation.…”
Section: Flexible Endoscopic Examination Of Swallowingmentioning
confidence: 97%
“…A less common approach utilizes direct flexible nasopharyngoscopy to visualize the larynx during swallowing. The salivagram is a tool that specifically diagnoses salivary aspiration when radiotracer placed in the buccal pouch is detected in the tracheobronchial tree [13].…”
Section: Evaluation Of Aspirationmentioning
confidence: 99%